Facial and Profile Changes After Orthodontic Retraction of Anterior Teeth in First Bicuspid Extraction Cases - Gadhiya, Nitin; Narkhede, Sameer; Sonawane, Sushma; Fegade, Anushree; Khamatkar, Aparna; Sawant, Veera; Chimankar, Shreenath (Journal of Neonatal Surgery, 2025)
Facial esthetics play a crucial role in orthodontics, where patients often evaluate treatment success by visible changes in their soft tissue profile. Bimaxillary protrusion, common in South Asian populations, is typically managed through extraction of four first premolars followed by anterior retraction. This retrospective observational study evaluated skeletal, dental, and soft tissue changes in 40 Class I Indian patients (mean age: 18.7 ± 2.3 years) treated with MBT fixed appliances after first premolar extractions. Pre- and post-treatment cephalograms were analyzed for skeletal (SNA, SNB, ANB), dental (1-NA, 1-NB, IMPA, 1-SN), and soft tissue parameters (lip position to TVL, nasolabial and labiomental angles, interlabial gap, soft tissue thickness). Results revealed significant upper and lower incisor retraction (p < 0.001), accompanied by notable soft tissue improvements: upper and lower lips retruded by ~3.3 mm, nasolabial angle increased by ~14°, labiomental angle improved by ~7°, and chin projection enhanced. Strong correlations were found between incisor retraction and lip response (r = 0.78–0.81), highlighting the predictability of soft tissue changes with dental movements. The findings confirm that extraction-based therapy in Class I bimaxillary protrusion yields favorable and esthetically balanced soft tissue outcomes. This study underscores the importance of incorporating soft tissue considerations into orthodontic treatment planning, particularly for Indian populations with distinct esthetic norms.